1990
DOI: 10.1098/rspb.1990.0030
|View full text |Cite
|
Sign up to set email alerts
|

Passive bipedal running

Abstract: Human-like running is a natural dynamic mode of a simple mechanical biped. Such a machine consists of two telescoping legs with linear springs, connected by a hip joint with a torsional spring. It will run passively; no pattern of forcing is required to generate the gait. With careful design its energy consumption can approach zero, but in any case the passive cycle can be ‘pumped' by various means to sustain running over a range of speeds and slopes. Passive running can also be realized over a wide range of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(70 citation statements)
references
References 8 publications
4
66
0
Order By: Relevance
“…Representations of the running leg as a simple spring have described the mechanics of a running leg remarkably well (2,11,12,15,16,18,19,(25)(26)(27). It has been shown that the physical musculoskeletal elastic components of the leg (tendons, ligaments, and muscles) are used to minimize metabolic cost while running (1,2,(8)(9)(10).…”
Section: In Their Groundbreaking Work Mcmahon and Greenementioning
confidence: 99%
“…Representations of the running leg as a simple spring have described the mechanics of a running leg remarkably well (2,11,12,15,16,18,19,(25)(26)(27). It has been shown that the physical musculoskeletal elastic components of the leg (tendons, ligaments, and muscles) are used to minimize metabolic cost while running (1,2,(8)(9)(10).…”
Section: In Their Groundbreaking Work Mcmahon and Greenementioning
confidence: 99%
“…In walking, the body behaves like an inverted pendulum (McGeer, 1990a;Mochon & McMahon, 1980), yielding highly conservative exchanges of kinetic and potential energy. In running, the body behaves like a bouncing ball, in which kinetic energy is converted to elastic energy stored in the tendons and muscles of the stance leg (Blickhan, 1989;McGeer, 1990b;McMahon & Cheng, 1990). A transition from the pendular walking mode to the elastic running mode could be brought about by an increase in propulsive force in the stance phase that propels the body into the air.…”
Section: Theories Of Gait Transitionsmentioning
confidence: 99%
“…Elastic couplings acting as return springs have first been used solely in passive dynamic running [29,38]. Later an elastic coupling in the form of a hip spring was also used in spatial passive dynamic walking to adjust the step frequency to the frequency of the toddling motion for stabilization [26].…”
Section: Introductionmentioning
confidence: 99%